Phosphorylation of Mycobacterium tuberculosis ParB Participates in Regulating the ParABS Chromosome Segregation System - Baronian, Grégory (PLoS One, 2015)
Here, we present for the first time that Mycobacterium tuberculosis ParB is phosphorylated by several mycobacterial Ser/Thr protein kinases in vitro. ParB and ParA are the key components of bacterial chromosome segregation apparatus. ParB is a cytosolic conserved protein that binds specifically to centromere-like DNA parS sequences and interacts with ParA, a weak ATPase required for its proper localization. Mass spectrometry identified the presence of ten phosphate groups, thus indicating that ParB is phosphorylated on eight threonines, Thr32, Thr41, Thr53, Thr110, Thr195, and Thr254, Thr300, Thr303 as well as on two serines, Ser5 and Ser239. The phosphorylation sites were further substituted either by alanine to prevent phosphorylation or aspartate to mimic constitutive phosphorylation. Electrophoretic mobility shift assays revealed a drastic inhibition of DNA-binding by ParB phosphomimetic mutant compared to wild type. In addition, bacterial two-hybrid experiments showed a loss of ParA-ParB interaction with the phosphomimetic mutant, indicating that phosphorylation is regulating the recruitment of the partitioning complex. Moreover, fluorescence microscopy experiments performed in the surrogate Mycobacterium smegmatis ΔparB strain revealed that in contrast to wild type Mtb ParB, which formed subpolar foci similar to M. smegmatis ParB, phoshomimetic Mtb ParB was delocalized. Thus, our findings highlight a novel regulatory role of the different isoforms of ParB representing a molecular switch in localization and functioning of partitioning protein in Mycobacterium tuberculosis.